Transformation of Pesantren Leadership: From Charismatic to Participatory Leadership at Madinatul Munawwarah Islamic Boarding School, Bukittinggi - Mustaqim; Junaidi; Febrino (Sustainable, 2026)
This study aims to analyze the transformation of leadership at Madinatul Munawwarah Islamic Boarding School (Pesantren), Bukittinggi from a charismatic leadership model to a participatory leadership model. The research employed a qualitative approach using data collection techniques through interviews, observations, and documentation. The research informants consisted of senior teachers, pesantren leaders, and alumni. The findings revealed that the charismatic leadership led by Buya Pimpinan from 2001 to 2022 had a significant influence on the development of the pesantren. This can be seen from the substantial increase in the number of students from 13 in 2001 to 453 in 2021. Buya’s charismatic leadership was characterized by exemplary conduct, authority, depth of knowledge, and the ability to unite all elements of the pesantren. After the passing of Buya Pimpinan in May 2022, the leadership of the pesantren transformed into a more participatory model by involving the vice leader and the head of the madrasah in decision-making processes. This transformation resulted in a more open and systematic organizational culture, although during the transition period the number of students declined. Nevertheless, conditions have begun to stabilize over the last two years. This study demonstrates that leadership transformation is an important process in maintaining the sustainability of Islamic educational institutions amid social changes and modern challenges.